Faktor Lingkungan yang Mendorong Perilaku Warga Lereng Merapi untuk Tidak Mengungsi - S Andarwati; F T Haryadi; T M Widi; N D Dono (Universitas Sebelas Maret (UNS), 2010)
Phenomenon of Merapi Mountain that the most active Strato mountain in Indonesia was interest to learn. There many explosion were threat of danger, not only human but include with property. Fact, there many people in the dangerous Merapi area were not escape from the area when Merapi showed raising activity. The research conduct to determine environment factors were motivated people on Merapi slope not to flee. The method used by descriptive analysis, data were taken with survey, the respondent of survey taken by purposive random sampling method. The result showed that: 1) Effort to defend economics asset as the main source of family income, dairy cattlein the case, because of there’s no good evacuation stable for cattle, 2) Experiences of the past, there were none human killed or property loss in their village and 3) People’s believe for generation that his area was not in dangerous because it stand in front of the mountain; were motivated people on Merapi slope not to flee.Key words : Environment, Merapi, flee, animal